2020
DOI: 10.1021/acs.langmuir.0c02476
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Dependent Surfactant Transport on the Microscale: Interfacial Tension and Droplet Coalescence

Abstract: Liquid−liquid emulsion systems are usually stabilized by additives, known as surfactants, which can be observed in various environments and applications such as oily bilgewater, water-entrained diesel fuel, oil production, food processing, cosmetics, and pharmaceuticals. One important factor that stabilizes emulsions is the lowered interfacial tension (IFT) between the fluid phases due to surfactants, inhibiting the coalescence. Many studies have investigated the surfactant transport behavior that leads to cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 105 publications
2
18
0
Order By: Relevance
“…The interfacial tensions between water and cyclohexane containing 0.02 g/mL of Span 80 ® rises from 6.30 ± 0.03 mN/m to 6.58 ± 0.13 mN/m upon adding in 10 wt% of CTAB. A similar finding was reported by Chen et al (2020) in a study of the stability of dispersed droplets in light mineral oil containing Span 80 ® [ 42 ]. It was found that the droplets tended to coalesce as the interfacial tension of the immiscible liquids increased, leading to the formation of larger particles [ 42 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The interfacial tensions between water and cyclohexane containing 0.02 g/mL of Span 80 ® rises from 6.30 ± 0.03 mN/m to 6.58 ± 0.13 mN/m upon adding in 10 wt% of CTAB. A similar finding was reported by Chen et al (2020) in a study of the stability of dispersed droplets in light mineral oil containing Span 80 ® [ 42 ]. It was found that the droplets tended to coalesce as the interfacial tension of the immiscible liquids increased, leading to the formation of larger particles [ 42 ].…”
Section: Resultssupporting
confidence: 87%
“…A similar finding was reported by Chen et al (2020) in a study of the stability of dispersed droplets in light mineral oil containing Span 80 ® [ 42 ]. It was found that the droplets tended to coalesce as the interfacial tension of the immiscible liquids increased, leading to the formation of larger particles [ 42 ]. Moreover, the particle size of polymer is affected by different surfactant types.…”
Section: Resultssupporting
confidence: 87%
“…B2 had the highest F max . Although there have been reports that the dynamic IFT of a droplet can be size-dependent, , the diffusion of surface-active molecules from the bulk to the interface played important roles in causing such differences. By applying a different bulk concentration in the simulations to effectively ″expedite″ the diffusion, we might have reached a similar surface coverage at the water/toluene interface as compared to experiments, which led to the good qualitative comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, surface tension measurements of liquids are performed via force-based measurements, i.e., Wilhelmy plate 19 and du Nouÿ ring, 19 pressure-based approaches, i.e., pendant drop, 20 (maximum) bubble pressure, 21 and spinning drop method, 22 and so on. 23 For the measurement of metals, the surface tension is measured via sessile drop, 24 pendant drop, 25 and levitated drop methods 26 in a high-temperature furnace, while oxygen is excluded. A prerequisite for these methods is that an equilibrium is established in the time scale of the experiment.…”
Section: Introductionmentioning
confidence: 99%